Kehujjahan dan Kualitas Suatu Hadist - Juli Julaiha P; Vena Annisa Harahap; Nurul Annisa Khaidir; M. Ridho Alfattah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article presents opinions from several literatures regarding the quality and validity of a hadith as a source of Islamic law. The validity and quality of a hadith in its stipulation in Islamic law is divided into three, namely authentic hadis, which are hadiths that are continuous with the sanad, narrated by narrators who are 'fair and dabit, avoid shadh and 'illat. Hasan hadiths are hadiths narrated by fair narrators, lack strong memorization, continuous sanad, do not contain 'illat and do not contain syaz. Daif hadith, an-Nawawi defines a daif hadith as a hadith in which there are no valid hadith requirements and hasan hadith requirements. The position of hadith in law ranks second after the Koran, because the contents of the Koran sometimes require more explanation for Muslims, so the hadith in its position and function is very important